2016
DOI: 10.1111/jep.12634
|View full text |Cite
|
Sign up to set email alerts
|

Cost of treatment of peripheral neuropathic pain with pregabalin or gabapentin in routine clinical practice: impact of their loss of exclusivity

Abstract: To analyze the effect of loss of exclusivity of data on the cost of treatment of peripheral neuropathic pain (PNP) with pregabalin or gabapentin in routine clinical practice. A retrospective observational study, with electronic medical records for patients enrolled at primary care centers managed by the health care provider Badalona Serveis Assistencials, who initiated treatment of PNP with pregabalin or gabapentin. The analysis used drugs and resources prices for year 2015. The 1163 electronic medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Neuropathic pain such as postherpetic neuralgia, post-stroke pain, and trigeminal neuralgia is known to occur as a result of peripheral and/or central neurological disturbances [1]. Neuropathic pain is also clinically typified by intractable non-noxious stimulation-induced pain and thought to be a direct result of a lesion or disease that affects the peripheral somatosensory system [2]. In clinical practice, spinal cord stimulation (SCS) has been well established as a safe and effective treatment of chronic, intractable pain including neuropathic pain [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain such as postherpetic neuralgia, post-stroke pain, and trigeminal neuralgia is known to occur as a result of peripheral and/or central neurological disturbances [1]. Neuropathic pain is also clinically typified by intractable non-noxious stimulation-induced pain and thought to be a direct result of a lesion or disease that affects the peripheral somatosensory system [2]. In clinical practice, spinal cord stimulation (SCS) has been well established as a safe and effective treatment of chronic, intractable pain including neuropathic pain [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Several therapies are available for neuropathic pain but pregabalin is the only treatment licensed in the United States (US) and Europe for the treatment of both central and peripheral neuropathic pain. It is often used as a first-line treatment in clinical practice due to its favorable pharmacokinetic profile and potency [4]. The common use of pregabalin is reflected in the prescribing rates, which increased by 17.2% in the United Kingdom (UK) alone between 2013 and 2016 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although they differ in their pharmacokinetic properties and formulations, in clinical trials both drugs have demonstrated the capacity to reduce PNP, with similar tolerability profiles [7]. Nevertheless, under routine clinical practice conditions, significant differences have been noted between the two molecules in the treatment of chronic PNP depending on whether branded or generic versions of the same active substance are used [8], with loss of exclusivity of the drugs' reference prices [9], and even the effects of age and gender on clinical and economic consequences in the treatment of PNP [8,10]. Some patients do not receive the appropriate pharmacological treatment, or the doses prescribed are lower than recommended doses [1,2,5,6,11,12].…”
mentioning
confidence: 99%